Preconcentration of Cr(III) Using Dowex 50WX2-200 Resin and Its Application to River Water - Siti Nuraini; Suheryanto Suheryanto; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Cr(III) is one of the most stable chromium species in nature, Cr(III) species are not carcinogenic to humans, but if the levels in the body exceed 0.2 mg / day it is very dangerous for the body especially in the respiratory tract. The presence of chromium in the aquatic environment is so low that it is very difficult to detect it using instruments with various limitations to detect it, therefore preconcentration techniques are carried out to overcome the issue. In this study the water sample was adjusted pH using HNO3 0.1 M or NaOH 0.1 M, after which it was passed in the dowex column 50WX2-200. Furthermore, an elution process was carried out using the 1 M HNO3 eluent, the eluat was measured for absorbance with flame AAS. The results of Cr(III) preconcentration optimization are: resin weight 0.5 g, HNO3 eluent concentration 1 M, solution pH 3 and sample volume 50 – 100 mL. The Cr(III) preconcentration technique using Dowex 50WX2-200 resin has been applied to river water samples with a detectable concentration of 0.0075 mg/L.